Heat Exchangers in Carnot Batteries: Condensation and Evaporation in a Reversible Device - Steger, Daniel; Regensburger, Christoph; Pham, Vu Jenny; Schlücker, Eberhard (Energies, 2021)
The combined heat pump-organic Rankine cycle is a thermal-electrical storage concept which allows the reversible use of components in both operation modes (loading and unloading the storage). This saves in terms of investment costs but also creates challenges during design and operation. A heat exchanger is an expensive component destined to be used for the reversible purposes of a heat pump condenser and an organic Rankine cycle evaporator. In this study, the operation of such an apparatus was evaluated based on an analytical model, experimental data and thermal imaging. This study shows that the model can predict the filling of the apparatus distinguished by liquid, vapour and the two-phase region. The thermal imaging supports the model and gives the location of the regions. Connecting both methods, a valid statement about the current condition of the heat exchanger is possible. Due to very small pinch points, the apparatus is not efficiently used in the investigated modes. Extending the pinch to 2 K can already save up to 46.1% of the heat exchange area. The quality of the heat transfer in the evaporator (qORC = 10.9 kW/m(2)) is clearly higher than in the condenser (qHP = 6.1 kW/m(2)).
CRIS-Team WoS Importer:2021-10-08